Ответы и объяснения

2013-11-23T07:10:28+00:00
А) (х(х+1)-х)/(х+1)=(x^2+x-x)/(x+1)=x^2/(x+1)
б)=((m+2)(m+4)-4m) / (4m(m+4))=(m^2+6m+8-4m)/(4m(m+4)=(m^2+2m+8)/(4m^2+16m)
г) =(3x+y)/(x(x+y))-(x+3y)/(y(y+x))=((3xy+y^2-x^2-3xy)/(xy(x+y))=(y^2-x^2)/(xy(x+y))((y-x)(y+x))/(xy(x+y))=(y-x)/xy
в)=(x(x-y)+y(x+y))  /((x+y)(x-y))=(x^2-xy+xy+y^2)/(x^2-y^2)=(x^2+y^2)/(x^2-y^2)
2) a)(x-9)/((x-3)(x+3))-3/(x(3-x))=(x^2-9x+3x+9))/(x(x-3)(x+3))=(x^2-6x+9)/(x(x^2-9)=((x-3)^2)/(x(x-3)(x+3))=(x-3)/(x^2+3x)
2) б) 1/(х-2)-6х /((х-2)(x^2+2x+4))=(x^2+2x+4-6x^2+12x)/((x-2)(x^2+2x+4))=(-5x^2-14x+4) /((x-2)(x^2+2x+4))=
2) b)=3/x+21/(x(x-7)-(4-x)/(x-7)=(3(x-7)+21-4x+x^2) /(x(x-7))=(3x-21+21-4x-x^2)/(x(x-7))=(-x-x^2)/(x(x-7))=-x(x+1)) /(x(x-7)=(x+1)/(7-x)
спасибо!!!!!!!!